Three-dimensional hierarchical porous carbon coupled with chitosan based electrochemical sensor for sensitive determination of niclosamide. (1st January 2022) - Li, Fang; Liu, Runqiang; Dubovyk, Volodymyr; Ran, Qiwen; Li, Bo; Chang, Yuqi; Wang, Hongliang; Zhao, Hongyuan; Komarneni, Sridhar
Highlights: 3D porous carbon@chitosan composite was prepared by ultrasonic-assisted green method. 3D porous carbon shows conductive network, high surface area, and functional groups. A composite sensor was fabricated for the determination of niclosamide. 3DHPC@CTS/GCE sensor showed good niclosamide detection performance in food samples. A very low detection limit of 6.7 nM niclosamide was achieved at the modified sensor. Abstract: Herein, a simple, low-cost, environment-friendly strategy was proposed to prepare the composite of three-dimensional hierarchical porous carbon and chitosan, which was applied to modify the glass carbon electrode to fabricate an electrochemical sensor for the determination of niclosamide. The three-dimensional porous carbon with interconnected conductive network, high surface area, and self-generated oxygen-containing functional groups was prepared by salt-templating method with glucose as carbon source and eutectic mixture of LiBr/KBr as both activating and pore-forming agent. During the subsequent ultrasonic process, chitosan with excellent filming property, strong adsorption ability, and good dispersibility was successfully decorated on the obtained porous carbon to further enhance the determination performance of niclosamide. Benefitting from the multi-functional integration of three-dimensional hierarchical porous carbon and chitosan, the fabricated sensor presented a low limit of detection (6.7 nM) in the linear concentration range from 0.01 to 10 µM. Moreover, the fabricated sensor could show good repeatability, reproducibility, stability, and selectivity. Most important, the decent practicability for the detection of niclosamide was obtained in different food samples with low relative standard deviation and satisfactory recoveries. This work provides a very valuable reference for the sensitive determination of niclosamide in food samples.